The effect of ozone therapy in root canal disinfection: a systematic review. (3rd November 2019) - Silva, E. J. N. L.; Prado, M. C.; Soares, D. N.; Hecksher, F.; Martins, J. N. R.; Fidalgo, T. K. S.
Abstract: Aim: To answer the following focused question: 'As regards microorganism load reduction for patients undergoing root canal treatment, is the use of ozone therapy comparable to conventional chemomechanical techniques using sodium hypochlorite (NaOCl)?' Data sources: A systematic review was conducted using controlled vocabulary and free‐text key words in the following databases: PubMed, Science Direct, Scopus, Web of Science and Open Grey until 2 November 2018. Additional studies were sought through hand searching of endodontic journals. Study eligibility criteria, participants and interventions: The inclusion criteria comprised studies that compared microbial reduction in root canals after treatments with ozone and NaOCl in extracted mature human teeth or randomized clinical trials. Study appraisal and synthesis methods: The quality assessment of included laboratory studies was performed with the following parameters: (i) sample size calculation, (ii) samples with similar dimensions, (iii) control group, (iv) standardization of procedures, (v) statistical analysis and (vi) other risk of bias. For randomized clinical trials, the qualitative analysis of the studies was performed from the bias risk assessment using the tool 'Bias Risk Assessment of Randomized Controlled Studies' Cochrane Handbook 5.0.2. Results: The search resulted in 180 published studies. After removal of duplicate studies and full‐text analysis, eight studies were selected and seven were considered low risk of bias (seven ex vivo studies and one random clinical trial). Overall, the results demonstrated that ozone therapy provides significantly less microbial load reduction than NaOCl. As an adjunct in chemomechanical preparation, ozone was ineffective in increasing the antimicrobial effect of NaOCl. Ozone performance was strongly associated with the application protocol used: it is dose, time and bacterial strain dependent, besides the correlation with the use of complementary disinfection sources. Limitations: A restricted number of randomized clinical trial was found, and the difference amongst the methodology of the studies did not allow a meta‐analysis to be performed. Conclusions and implications of key findings: Although the selected studies had limitations, this review reached a satisfactory methodological and moderate evidence quality contributing to important preliminary information regarding ozone therapy. As regards load reduction of microorganisms for patients undergoing root canal treatment, ozone is not indicated neither to replace nor to complement the antimicrobial action of NaOCl.